Resource use and strategies for development of pastoral systems in subhumid West Africa - The case of Nigeria - Bayer, W.; Suleiman, H.; Kaufmann, Ralph R. von; Waters-Bayer, Ann (1987)
Outlines the major elements of pastoral resource use and examines strategies for development of pastoral systems in subhumid west Africa. Looks at cattle management, grazing resources, transhumant cattle, grazing reserves, and ranching.